1986
DOI: 10.1161/01.str.17.3.460
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion after cerebral ischemia: influence of duration of ischemia.

Abstract: SUMMARYThe influence of the duration of ischemia on the pattern of cerebral blood flow in recirculation was studied in anesthetised rats. Severe incomplete cerebral ischemia (mean ischemic flow = 5.8 ± 0.4 ml/100 g/min) was produced by four-vessel occlusion and recirculation permitted after 15,30 or 60 minutes ischemia. All three groups showed an immediate hyperemia followed by hypoperfusion. Hyperemia was maximal following 15 minutes ischemia and least pronounced following 60 minutes ischemia (p = 0.0249). Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
3

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 58 publications
2
24
1
3
Order By: Relevance
“…reperfusion into a maximally vasodilated arterial bed (Dirnagl et al, 1994;Todd et al, 1986). In this context, it has been suggested that recovery of vascular smooth muscle tone may contribute to subsequent hypoperfusion (Todd et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reperfusion into a maximally vasodilated arterial bed (Dirnagl et al, 1994;Todd et al, 1986). In this context, it has been suggested that recovery of vascular smooth muscle tone may contribute to subsequent hypoperfusion (Todd et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has been suggested that recovery of vascular smooth muscle tone may contribute to subsequent hypoperfusion (Todd et al, 1986). Animal studies have shown that ultrasound application can significantly improve tissue perfusion in rabbit muscle and myocardial ischemia after fixed arterial occlusion (Siegel et al, 2004;Suchkova et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, however, Smith et al (12) showed that some mor phological damages developed in the cerebral cortex during the 7-day recovery period fol lowing 4 to 10-min ischemia in the rat Transient cerebral ischemia is known to be followed by regionally heterogeneous circula tory disturbances such as the no-reflow phenomenon (1.3-15) and the post-ischemic hypoperfusion syndrome (15)(16)(17)(18)(19)(20), which may disturb functional recovery of the brain. Therefore, another possible explanation would be that the degree of post-ischemic hypoperfusion in the baroreflex pathway might be greater than that in the cerebral cortex, resulting in the selective attenuation of the baroreflex activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although many models of global cerebral ischemia have been reported in gerbils (Yoshida et al, 1980), rats (Pulsinelli and Brierley, 1979;Todd et al, 1986), cats (Paschen et al, 1983), dogs (Jackson and Dole, 1979), and the primates (Branston et al, 1980), we consider that the rabbit should be chosen as the best candidate for the model of CPIR because the pattern of brain vessels in the rabbit is more similar to that in the primates and man than that in dogs and cats (Aguilar, 1963;Gu, 1983). In addition, the rabbit's size is bigger than rats, so it is easier to measure intracranial pressure, blood pressure, and to take more blood samples.…”
Section: Introductionmentioning
confidence: 99%